2022
DOI: 10.1007/s40200-022-01141-w
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health inequity in Iran: a narrative review

Abstract: Objective COVID-19 burden the health system by influencing several aspects of social determinants of health (SDH). We review SDH inequity in Iran with notice on COVID-19 pandemic and sanctions. Method The Databases such as MEDLINE, Scopus, and Google Scholar were searched. The SDH components were extracted regarding the effect of COVID-19 and sanctions. Global burden of disease was used to evaluate the impact of sanctions on mortality in Iran. Result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The higher prevalence of urolithiasis observed among Baluch people may be attributed to risk factors unaccounted for in this study, such as the lower socioeconomic development in Sistan and Baluchestan province and also the established genetic distinction between Baluch ethnicity and the other Iranian ethnicities. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of urolithiasis observed among Baluch people may be attributed to risk factors unaccounted for in this study, such as the lower socioeconomic development in Sistan and Baluchestan province and also the established genetic distinction between Baluch ethnicity and the other Iranian ethnicities. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…The coincidence of the last 2 years of this program with the start of the Covid‐19 pandemic in the world and in Iran may have been one of the factors affecting it. Covid‐19 pandemic has affected the CHE index in various ways, such as increasing health costs, increasing unemployment, weakening the household's economic status, and reducing the household's ability to pay 24–26 . In addition, in recent years, Iran has had a growing inflation, which can also be a reason for that 27–29 …”
Section: Discussionmentioning
confidence: 99%
“…Covid-19 pandemic has affected the CHE index in various ways, such as increasing health costs, increasing unemployment, weakening the household's economic status, and reducing the household's ability to pay. [24][25][26] In addition, in recent years, Iran has had a growing inflation, which can also be a reason for that. [27][28][29] According to the findings of another systematic and metaanalysis study in Iran (2017), the prevalence of households faced with CHE was reported to be 3.9% (95% CI, 3.26−11.07).…”
Section: Discussionmentioning
confidence: 99%
“…Like many countries, Iran grapples with disparities across various social determinants of health-related issues [ 9 ]. A cross-sectional study conducted in Iran revealed a significant disparity in the health outcomes of COVID-19-infected patients between urban and suburban areas [ 10 ].…”
Section: Introductionmentioning
confidence: 99%